2015
DOI: 10.1121/1.4916794
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo experiment for measuring acoustic properties of macroalgae living tissue

Abstract: A methodology is developed to measure ex situ ultrasonic velocity of submerged aquatic vegetation tissue, in particular, macroalgae, in a nondestructive and efficient manner. An entire thallus is submerged in artificial seawater-filled tank through which many ultrasonic pulse-echo measurements are recorded while thallus parts are randomly displaced. Average sound speed of tissue is estimated from normal fit to extracted travel times given measured total volume fraction of tissue and travel time in water alone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Moreover, ultrasonic experiments 13,14 on the macroalgae Ecklonia radiata indicated that the internal cell structure can have a significant impact on the acoustic response when they showed a 30 m/s difference in sound speed between blade tissue, where the cells are tightly packed, and stipe tissue, where the cells are loosely packed. A direct relationship between any of the physical differences within a seagrass species and the effective sound speed of the blades would provide another ecological parameter for acoustic remote sensing and take us one step closer to a forward model for sound propagation through seagrass meadows.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, ultrasonic experiments 13,14 on the macroalgae Ecklonia radiata indicated that the internal cell structure can have a significant impact on the acoustic response when they showed a 30 m/s difference in sound speed between blade tissue, where the cells are tightly packed, and stipe tissue, where the cells are loosely packed. A direct relationship between any of the physical differences within a seagrass species and the effective sound speed of the blades would provide another ecological parameter for acoustic remote sensing and take us one step closer to a forward model for sound propagation through seagrass meadows.…”
Section: Resultsmentioning
confidence: 99%
“…Single-beam and split-beam echosounders operating at 120 kHz or 200 kHz have been used to detect the presence of kelp [19], measure its canopy height [20], or map its distribution [21][22][23][24]. The availability of strict but practical calibration protocols [25], standard data processing methods [26], and laboratory measurements of acoustic properties of kelp [27][28][29][30] may even allow using these systems to estimate kelp biomass. However, these systems have a limited angular aperture (usually of the order of 1-10 • ), which results in a very limited spatial coverage.…”
Section: Introductionmentioning
confidence: 99%